Explorations of Personality: A Psychoanalytic Study of Ibsen’s Hedda Gabler - Bhatta, Arjun Dev (The Batuk, 2023)
Personality is the combination of behavior, emotion, feeling, motivation, and thought patterns that define an individual. People differ from each other in terms of their personalities and character traits. The unique personality of an individual is based on both internal and external factors which make people act, behave, and perceive the world differently from others. This research paper attempts to expose the personalities of the characters in Henrik Ibsen’s play Hedda Gabler. However, this article observes in detail the eccentric and unusual behavior of the female protagonist Hedda Gabler. Attempts have been made to investigate the various circumstances responsible for shaping her odd personality. Moreover, it analyzes Hedda’s psyche in the light of psychoanalytic theory proposed by psychologists such as Sigmund Freud, Erik Erikson, Karl Jung, and Karen Horney.